Developing the business-society nexus through corporate responsibility expectations in India. Issue 2 (23rd January 2019) - Bergman, Zinette; Teschemacher, Yael; Arora, Bimal; Sengupta, Rijit; Leisinger, Klaus Michael; Bergman, Manfred Max
Abstract : Purpose: The Government of India dramatically altered the dynamic between business and society when it introduced the Companies Act 2013, which mandated firms to expend at least 2 per cent of average net profits on corporate responsibility (CR) programmes. This reconfiguration of social value creation may serve as a template for a closer and participatory relationship between the private sector and government in emerging economies and beyond. This paper aims to analyse how CR expectations have taken shape in the print media in India. Specifically, the authors ask the following: What are the dimensions of CR expectations in mainstream Indian newspapers?, and Why, according to the newspaper narratives, do corporations have these responsibilities? Design/methodology/approach: In this qualitative study, the authors randomly selected and analysed 50 per cent ( n = 442) of the newspaper articles that dealt explicitly with CR. The articles appeared in the top five Indian English-language newspapers and the top two Hindi-language newspapers between 1 January and 31 December 2015. Using Content Configuration Analysis (CCA), the authors developed a typology of CR expectations and analysed their associated justifications. Finally, they used CCA to analyse how this typology and its justifications connect to the two main stakeholders: the business sector and government. Findings: The analyses reveal how the introduction of the Companies Act 2013 had a major impact on CR expectations by explicitly and legally casting the business sector as the engine of social development. The authors were able to describe how contextual and cultural dimensions frame evolving interests and societal demands towards corporations, and how difficult it may be for corporations to fulfil CR expectations that are well beyond their core business and that reach domains usually pertaining to government. Originality/value: This study contributes an empirical exploration of media discourse on contemporary CR expectations in India and its associated notions of social value creation, and how these are shaped by various cultural and contextual influences. The authors discuss how this novel approach to CR modifies the relations between business and society, and they reflect on the opportunities and limits of this model for other emerging economies, which struggle to formulate a symbiotic relationship between business and society.